Assessment the effects of Mastic Gum Resin, Lawsonia Inermis and Quercus Brantii on Cutaneous Wound Healing in BALB/c Mice - Kwestan Najm Ali1, Hardi Fattah Marif1 , Hana Sherzad Raoof1 , Snur M. A. Hassan2 , Dereen Omer Ra (Institute of Medico-legal Publications Pvt Ltd, 2021)
The request for more efficient and lower-cost therapeutic methods for wound healing remains a challengefor modern medicine. The goals of this investigation were to recognize and look at the impacts of MasticGum Resin, Lawsonia Inermis, and Quercus Brantii in wound healing by using histopathological study andblood parameters in BALB/c Mice. Mice were comprised into four groups: Control negative group (n=10),mice were not treated with plant suspension only applied with normal saline; Treatment group I, mice wereapplied by Mastic Gum Resin (MGR) (n=10), Treatment group II, mice were applied with the QuercusBrantii (n=10), and the last group, Treatment III which were applied with Lawsonia Inermis (LI) (n=10).One ml for each suspension of Mastic Gum Resin (MGR), Quercus Brantii (QB), and Lawsonia Inermis(LI) was applied to the wound directly without suturing for 4 days/week for about 3 weeks. Wound healingeffects were evaluated by utilizing the hematological profile for each group with the histopathological study.The cutaneous wound in Mastic Gum Resin and Quercus Brantii treated groups were more effective inprogressing wound healing than Lawsonia Inermis treated group regarding histological changes at day 8 andday 18, respectively and blood parameters at day 21.